PECULIARITIES OF THE USE OF PHOTOELECTRON MULTIPLIERS (PHEM) - Pereversentsev, A. F.; Ivanov, V. N.; Ryabov, A. V.; Lisova, L. E. (Одеські астрономічні публікації, 2012)
Particular recommendations are given on the use of PHEM in the photon count regime.